Assessment of students learning capability adapting activity based learning – STAD - Bridjeshpappula (International Journal of Psychosocial Rehabilitation, 2020)
Current educational approaches within higher education utilize blended learning. Students receive a combination of traditional face to face instruction in class and are also required to complete activities outside of the class, facilitated through a range of technological resources. The purpose of this study is to provide a comprehensive overview of activity based learning. Blended learning has become increasingly popular in higher education globally, forming the cornerstone of curriculum design and providing opportunity for learning not previously possible or available to students. The results indicate that there is much indirect evidence emerging of improved academic performance and student and staff satisfaction with the STAD approach but a paucity of conclusive evidence that it contributes to building lifelong learning. It can be concluded from this study that activity based learning not only fosters the self learning of a learner but also allows the learner to learn according to one’s own skill and aptitude.